Kepemimpinan dan Kinerja Karyawan di Lingkungan PT. Antavaya Travel Area Bandung - Teddy Luthfi; DJ Suyaman; Sonny Hersona (Coopetition : Jurnal Ilmiah Manajemen, 2021)
Every organization or agency, both formal and informal, in carrying out programs that are directed to always be efficient to achieve agency goals. One way is to improve employee performance. Employees are Human Resources (HR) who are very important in determining progress and the creation of predetermined goals. In improving employee performance, supporting factors are needed including leadership. The study conducted by researchers at this time leads to an increase in employee performance at PT. Antavaya Corporate travel. Where is PT. Antavaya Corporate Travel is Indonesia's leading travel management company, helping companies of all sizes, multinationals and government agencies manage travel professionally and cost-effectively. Antavaya Corporate Travel is the largest Travel Management company in Indonesia. Founded in 1965, it has earned a reputation for quality service and professional management that is second to none. The core of the problem in this study is not yet optimal employee performance, and aims to 1) Knowing how leadership at PT. Antavaya corporate travel 2) Knowing how much influence leadership has on employee performance at PT. Antavaya corporate travel. The results showed that there was a significant influence between leadership on employee performance.